Principles of Islamic Education Management: The Perspective of the Qur'an and Hadith in Building Quality Education - Sinta Nurjanah; Acep Hermawan (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study explores the foundational principles of Islamic education management as articulated in the Qur'an and Hadith. It primarily aims to delve into the roles of planning, organizing, leadership, and supervision within the framework of these sacred texts, with the objective of enhancing the quality of education. Employing a literature review methodology, the study identifies, evaluates, and interprets pertinent research findings. A qualitative approach is utilized to synthesize the research results, integrating data to develop new theories or concepts and to foster a more profound and comprehensive understanding. Ultimately, the findings of this study highlight that Islamic education management seeks to effectively organize and optimize all available resources to achieve established goals in accordance with Islamic values. The basics of Islamic education management are the Qur'an, Hadith, and laws in force in Indonesia. This management process involves various main functions carried out by a manager or leader, namely: a) planning, b) organizing, c) leadership, d) supervision. The values contained in the Qur'an and Hadith show that the Prophet Muhammad SAW as an example of being a leader and manager, has applied management principles when leading which have proven to be effective and become a basis that can be applied in developing quality Islamic education with efficient and effective management, instilling character and morals and motivation and appreciation (rewards).